PENINGKATAN MUTU PENDIDIKAN MELALUI PROGRAM INTELEGENT CREATIVE (IC) - Achmad Maulidi; Musleh Musleh; Ghozi Mubarok (Dirosat : Journal of Islamic Studies, 2022)
Teachers are one of the most important elements in the field of education because teachers must play an active role in placing their position as professionals in accordance with what has been mandated by them, namely bringing students to a better future and making students a generation that can make the Indonesian nation an intelligent and creative nation in all fields.          This research uses a qualitative type of research pattern. The clumping of data in this study used observation, interview, and documentation techniques. For data analysis, descriptive analysis techniques are used in an attempt to make conclusions.          Based on the results of research conducted by researchers, it can be concluded: 1. Teacher Efforts in Improving the Quality of Education through (IC) (Intelligence Creative Education) at MA Al-Amien 1 Prenduan is to make plans in teaching and learning activities, hold activity programs for students outside of school hours or outside of school, schools provide the facilities needed by teachers and students in teaching and learning activities,  teachers try to find out the abilities of students in the classroom, take advantage of the facilities provided by the school, use varied and creative methods applied by teachers when teaching and learning activities take place, provide motivation to students who are lazy in class in teaching and learning activities. The inhibiting factors for teachers in improving the quality of education through (IC) (Intelligence Creative Education) at MA Al-Amien 1 Prenduan are first factors of facilities and infrastructure whose use is very limited and both student factors, when they have.At the end of learning, it is very difficult for teachers to raise the enthusiasm for learning for the students because at the end of learning this way the students are lazy to continue learning, because the level of student ability varies.